Corporate Governance And Tax Aggressiveness: Agency Theory Relationship - Bani Alkausar; Farel Badar Kawakibi; Mienati Somya Lasmana (Jurnal Reviu Akuntansi dan Keuangan, 2021)
The study aimed to provide evidence of whether corporate governance can lower the tendency of companies to perform tax aggressiveness. The term of Tax Aggressiveness was used to further expand the meaning of the act of minimizing taxes by companies. The cash effective tax rate was used as an indicator of the tax aggressiveness of companies. Meanwhile, corporate governance was measured by the institutional ownership, independent commissioner, audit committee, and audit quality. Samples used were the manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2018. Results of the 97 samples observed indicated that independent commissioners proved to be able to suppress the tendency of companies to commit Tax Aggressiveness; meanwhile, the institutional ownership, audit committee, and audit quality was not proven. The existence of the independent commissioners is able to influence the decisions in creating policies that are set by the management, so the management does not perform an opportunistic action that would benefit the management including committing Tax Aggressiveness.